2002
DOI: 10.1248/bpb.25.1247
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive Effect of Sesamin. IV. Inhibition of Vascular Superoxide Production by Sesamin.

Abstract: We previously demonstrated the preventive effect of sesamin, a lignan from sesame oil, on the development of several experimental models of hypertension. In the present study, we explored the mechanisms underlying the antihypertensive effect of sesamin using the deoxycorticosterone acetate (DOCA)-salt rat hypertensive model. After a 5-week treatment period, aortic superoxide (O 2 ؊ ) production was measured in the lucigenin chemiluminescence assay. Chemiluminescence signals significantly decreased in sesamin-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 14 publications
3
71
0
1
Order By: Relevance
“…Histopathological evidence of myocardial injury following IR injuries in sesame oil and captopril treated rat was also absent. Much research evidence suggests that the protective role of sesame oil against oxidative stress through its antioxidant mechanism (Kaur & Saini, 2000;Nakano et al, 2002;Hsu & Liu, 2004). It has been identified that presence of antioxidative principles like sesamin, sesamol and sesaminol might be a responsible components for its protective action (Suja et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Histopathological evidence of myocardial injury following IR injuries in sesame oil and captopril treated rat was also absent. Much research evidence suggests that the protective role of sesame oil against oxidative stress through its antioxidant mechanism (Kaur & Saini, 2000;Nakano et al, 2002;Hsu & Liu, 2004). It has been identified that presence of antioxidative principles like sesamin, sesamol and sesaminol might be a responsible components for its protective action (Suja et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…SO attenuates oxidative stress and multiple organ failure triggered by endotoxin lipopolysaccharide in rats [8] . Sesamin and sesaminol are the major phenolic constituents of SO which have been reported to possess a broad spectrum of pharmacological effects including antimutagenic [9] , antioxidant [10,11,12] ,antihypertensive [11] ,antiinflammatory [12] and antithrombotic [13] . This investigation was set to evaluate the protective effects of SO against DOX-induced cardiotoxicity in male rats and to study the mechanisms underlying these effects.…”
Section: Doxorubicinmentioning
confidence: 99%
“…Recently, much attention has been directed toward exploring the utilization of oilseeds in general [10] and sesame seed in special [11] for new food uses on the basis of their functional properties. Decorticated sesame seed can supply us with nutritious [3,6] functional [14] and healthy meals [8,12,13,18] with relatively low cost. The production of sesame-based dairy products can overcome the problems that limit consumption of soybased dairy products and other vegetable milk such as presence of anti-nutritional factors, Beany and astringent flavor low solids yield , Low dispersion stability flatulence factors [4,7,15] .…”
Section: Introductionmentioning
confidence: 99%